Analysis of different conditioned media secreted by limbal progenitor cells in the modulation of corneal healing. (February 2022) - Loureiro, Renata Ruoco; Cristovam, Priscila Cardoso; da Rosa, Larissa Rigobeli; Nova, Lucimeire; Gasparetto, Gustavo; Gil, Cristiane Damas; Gomes, José Álvaro Pereira
Abstract: Ex vivo cultivation and transplantation of limbal epithelial cells has been reported as an alternative source for ocular surface reconstruction. However, until now, the functional improvement of these patients is limited due to the low survival rate of the transplanted cells. Consequently, the clinical benefits of this therapeutic strategy are only temporary and can assign them to paracrine effects associated with the transplanted cells. With this background in mind, we aimed to analyze the effect of different conditioned media containing growth factors secreted by limbal progenitor cells on corneal epithelial healing, both in vitro and in vivo . Limbal tissue was used to obtain different conditioned media (CM). For the in vitro assay, corneal epithelial cells were treated with CM and the epithelial migration was analyzed. Growth factors in the CM were identified with ELISA and multiplex. For the in vivo assay in rats, total limbal stem cell deficiency (LSCD) was induced with an abrasive injury to the ocular surface, and the animals were treated with different CM. Clinical and histological analyses were performed. In the in vitro assay, treatment with limbal fibroblast (LF CM) was more effective compared to the other CM, and analysis revealed high concentrations of keratinocyte growth factor (KGF) and hepatocyte growth factor (HGF). In the in vivo assay, animals treated with LF CM showed epithelial defect improvement, maintenance of thickness, and decreased opacity and neovascularization. This treatment also allowed better ocular surface tissue organization when compared to the other treatments. The in vitro and in vivo experiments showed better outcomes in the corneal wound healing for the LF CM treatment. The high concentrations of KGF and HGF, linked to epithelial cell migration and proliferation, may correlate to the best results found in this treatment. Highlights: Conditioned media secreted by limbal progenitor cells in the modulation of corneal epithelial healing. Growth factors secreted by limbal fibroblast cells and their role in corneal epithelial healing. Biological modulation of corneal epithelial healing as a therapeutic strategy for the treatment of ocular surface diseases.